Post-Placental IUD Insertion: A Mixed Methods Assessment of Women's Experiences [22N]. (May 2016) - Carr, Shannon; Singh, Rameet; Espey, Eve; Sussman, Andrew; Rogers, Rebecca; Chungtuyco, Michelle
Abstract : INTRODUCTION: Studies examining patient-centered outcomes on post-placental intrauterine device (IUD) placement are currently lacking. The objectives of this study are: 1) describe women's experiences with post-placental IUD insertion through postpartum semi-structured interviews, 2) establish a mean pain score for the procedure using a 100 mm visual analogue scale (VAS), 3) assess insertional pain using a 4-point Likert verbal rating scale (VRS). METHODS: We enrolled women with and without an epidural in this concurrent mixed methods pilot study. Procedural pain was assessed using the VAS and VRS immediately after IUD placement and during the interviews. Interview data were coded and analyzed iteratively to identify emergent themes. Participants rated their overall satisfaction on a 5-point Likert scale. RESULTS: In the no epidural group 30 women underwent pain assessment and nine participated in an interview. In the epidural group 36 women underwent pain assessment and 12 participated in an interview. The median VAS scores were 40.5 mm and 2.8 mm in the no epidural and epidural groups, respectively. In the no epidural group, 53.3% of women reported none-mild pain. Most women (88.9%) in the epidural group reported none-mild pain. Women's satisfaction with the procedure was high in both groups. Convenience was the dominant decision-driver to undergo the procedure. Actual procedural pain and duration were less than expected among the majority of interviewees. CONCLUSION: Women who undergo post-placental IUD insertion report high satisfaction and no regrets about the procedure. Our study offers valuable counseling points to offer women if they are considering post-placental IUD placement.